Dynamics of brain iron levels in multiple sclerosis. (16th June 2015) - Khalil, Michael; Langkammer, Christian; Pichler, Alexander; Pinter, Daniela; Gattringer, Thomas; Bachmaier, Gerhard; Ropele, Stefan; Fuchs, Siegrid; Enzinger, Christian; Fazekas, Franz
<x xml:space="preserve">Abstract</x> Objective: We investigated longitudinal changes in iron concentration in the subcortical gray matter (caudate nucleus, globus pallidus, putamen, thalamus) of patients with clinically isolated syndrome (CIS) and definite multiple sclerosis (MS) and their relation to clinical and other morphologic variables. Methods: We followed 144 patients (76 CIS; median Expanded Disability Status Scale [EDSS] 1.0 [interquartile range (IQR) 0.0–2.0]; 68 MS; median EDSS 2.0 [IQR 1.0–3.3]) clinically and with 3T MRI over a median period of 2.9 (IQR 1.3–4.0) years. Iron concentration was determined by R2* relaxometry at baseline and last follow-up. Results: At baseline, subcortical gray matter iron deposition was higher in MS compared to CIS. In CIS, R2* rates increased in the globus pallidus (p < 0.001), putamen (p < 0.001), and caudate nucleus (p < 0.001), whereas R2* rates in the thalamus decreased (p < 0.05). In MS, R2* rates increased in the putamen (p < 0.05), remained stable in the globus pallidus and caudate nucleus, and decreased in the thalamus (p < 0.01). Changes in R2* relaxation rates were unrelated to changes in the volume of respective structures, of T2 lesion load, and of disability. Conclusions: Iron accumulation in the basal ganglia is more pronounced in the early than later phases of the disease and occurs independent from other morphologic brain changes. Short-term changes in iron concentration are not associated with disease activity or changes in disability.